2016
DOI: 10.1111/jfb.13052
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Atlantic salmonSalmo salarsperm: effects on sperm physiology

Abstract: The objective of this study was to determine the effect of freezing on the function in Atlantic salmon Salmo salar spermatozoa. The semen was frozen in Cortland's medium + 1.3M dimethyl sulphoxide + 0.3M glucose + 2% bovine serum albumin (final concentration) in a ratio of 1:3 (semen:cryoprotectant) as the treatment (T) and fresh semen as the control (F). Straws of 0·5 ml of sperm suspension were frozen in 4 cm of N2 L. They were thawed in a thermoregulated bath (40° C). After thawing, the percentage of sperma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 76 publications
(152 reference statements)
2
41
2
1
Order By: Relevance
“…(2015b) in European Perch and Figueroa et al. () in Atlantic Salmon. Different cryoprotectant and cryopreservation method combinations did not have a significant effect on sperm motility as there was no significant difference in motility between the cryopreserved treatment groups.…”
Section: Discussionmentioning
confidence: 94%
“…(2015b) in European Perch and Figueroa et al. () in Atlantic Salmon. Different cryoprotectant and cryopreservation method combinations did not have a significant effect on sperm motility as there was no significant difference in motility between the cryopreserved treatment groups.…”
Section: Discussionmentioning
confidence: 94%
“…Suquet et al (2016) reported 75% lower velocity in frozen/thawed spermatozoa of the great scallop compared to fresh. Linhart et al (2005) (Figueroa et al 2016), 97 µm s -1 to 134 µm s -1 in Prochilodus lineatus (Viveiros and Leal 2016;Viveiros et al 2017), 57 µm s -1 in rainbow trout Oncorhynchus mykiss (Suquet et al 2012b) and µm s -1 in Siberian sturgeon Acipenser baerii spermatozoa (Sarosiek et al 2014). VSL of sea urchin spermatozoa was shown to be 170-240 µm sec -1 in Hemicentrotus pulcherrimus (Hiramoto and Baba 1978) and 150-200 µm sec -1 in Paracentrotus lividus (Fabbrocini and D'Adamo 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Mystus nemurus [26,38], African catfish Clarias gariepinus [35,[39][40][41][42][43], giant goramy Osphronemus goramy [44,45], lampam Barbonymus gonionotus [46,47], salmonid spermatozoa [48][49][50][51][52], common carp Cyprinus carpio [53][54][55][56][57][58], zebra fish, Danio rerio [59][60][61][62][63] Mozambique tilapia, Sarotherodon mossambicus [64,65], rainbow trout, Oncorhynchus mykiss [66][67][68][69][70][71], and seurukan Osteochillus vittatus [72]. However, cryopreservation of botia sperm has never been reported previously.…”
Section: Several Species Of Fish Sperm Have Been Successfully Cryoprementioning
confidence: 99%